Energy Balance In Steel Liquefaction In Induction Furnaces And Electric Arc Furnaces - Sh.B. Tashbulatov, N.M. Saidmakhamadov.,; N.X. Tadjiev, N.X. Tadjiev; M.N.Gaybullaev, M.N. Gaybullaev (Indonesian Journal Publisher, 2020)
Various methods of liquefaction of steel are used all over the world; steelmaking in converter furnaces and steelmaking in electric arc furnaces and induction furnaces are two main areas among them. Steel production in electric furnaces is divided into steel production in induction furnace and electric arc furnace. In many countries, induction furnace liquefaction is common and is used mostly in private production enterprises. There is a large amount of literature on electric arc furnace steelmaking, and less information on induction furnace steelmaking. To study any process; the energy balance is preliminary. In this article, an attempt is made to express the energy balance of an induction furnace. The information is given in light of the processes of steel liquefaction at production enterprises. The data of the induction furnace were compared with other furnaces obtained from the literature. Various factors affecting energy input and output for both types of furnaces are discussed.